Listeria monocytogenes phosphatidylinositol (PI)-specific phospholipase C has low activity on glycosyl-PI-anchored proteins. - Gandhi, A J (1993)
The ability of the phosphatidylinositol-specific phospholipase C (PI-PLC) from Listeria monocytogenes to hydrolyze glycosyl phosphatidylinositol (GPI)-anchored membrane proteins was compared with the ability of the PI-PLC from Bacillus thuringiensis to hydrolyze such proteins. The L. monocytogenes enzyme produced no detectable release of acetylcholinesterase from bovine, sheep, and human erythrocytes. The cleavage of the GPI anchors of alkaline phosphatase from rat and rabbit kidney slices was less than 10% of the cleavage seen with the PI-PLC from B. thuringiensis. Activity for release of Fc gamma receptor IIIB (CD16) on human granulocytes was also low. Variations in pH and salt concentration had little effect on the release of GPI-anchored proteins. Our data show that L. monocytogenes PI-PLC has low activity on GPI-anchored proteins.